The Leading Causes of Death among Adult Mortality: Data Analysis of Sleman Health and Demographic Surveillance System, Indonesia - Abdul Wahab; Citra Indriani; Lutfan Lazuardi; Ningxin Zhu (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Determining the cause of death (CoD) is crucial for effective health policy and decision-making, particularly in population health programs. The World Health Organization (WHO) developed the Verbal Autopsy (VA) tool to ascertain CoD through verbal information, particularly in countries lacking comprehensive vital registration systems. In Indonesia, the health landscape is shifting from communicable diseases to non-communicable diseases (NCDs), highlighting the need for updated mortality surveillance. This study aimed to determine the major causes of death among adult mortality in Sleman Health and Demographic Surveillance System (HDSS) Indonesia. A demographic surveillance system was employed to monitor vital events, including mortality, with verbal autopsy interviews conducted for each death. A total of 279 adult deaths (ages 15 years and older) from the first two cycles of surveillance were analyzed. Trained enumerators conducted verbal autopsy interviews with informants close to the deceased. The InterVA program was used to process the verbal autopsy data, identifying the CoD for 274 adult deaths. Descriptive analysis was performed to determine the proportion of each cause of death, and Chi-square tests were used to assess differences in proportions. The findings revealed that 68.2% (95% CI: 62.38–73.72) of deaths were due to NCDs, including stroke, heart disease, diabetes, asthma, and chronic liver disease. Infectious diseases accounted for 24.8% (95% CI: 19.82–30.37), while injuries (primarily accidents) contributed to 6.6% (95% CI: 3.94–10.18). Stroke was the leading cause of death, particularly in individuals aged 50–64 years (21.2%, 95% CI: 16.48–26.49), followed by acute respiratory infections, including pneumonia (10.6%, 95% CI: 7.2–14.85). The study concluded that NCDs, particularly stroke, are the leading causes of adult mortality in Sleman HDSS, with significant contributions from acute respiratory infections and injuries. It is recommended for future research to further develop Verbal Autopsy technology, such as AI-based applications that can improve the accuracy of determining the cause of death.